Oral treponeme major surface protein: Sequence diversity and distributions within periodontal niches. (26th June 2017) - You, M.; Chan, Y.; Lacap‐Bugler, D.C.; Huo, Y.‐B.; Gao, W.; Leung, W.K.; Watt, R.M.
Summary: Treponema denticola and other species (phylotypes) of oral spirochetes are widely considered to play important etiological roles in periodontitis and other oral infections. The major surface protein (Msp) of T. denticola is directly implicated in several pathological mechanisms. Here, we have analyzed msp sequence diversity across 68 strains of oral phylogroup 1 and 2 treponemes; including reference strains of T. denticola, Treponema putidum, Treponema medium, ' Treponema vincentii ', and ' Treponema sinensis '. All encoded Msp proteins contained highly conserved, taxon‐specific signal peptides, and shared a predicted 'three‐domain' structure. A clone‐based strategy employing ' msp ‐specific' polymerase chain reaction primers was used to analyze msp gene sequence diversity present in subgingival plaque samples collected from a group of individuals with chronic periodontitis (n=10), vs periodontitis‐free controls (n=10). We obtained 626 clinical msp gene sequences, which were assigned to 21 distinct 'clinical msp genotypes' (95% sequence identity cut‐off). The most frequently detected clinical msp genotype corresponded to T. denticola ATCC 35405 T, but this was not correlated to disease status.UniFrac andlibshuff analysis revealed that individuals with periodontitis and periodontitis‐free controls harbored significantly different communities of treponeme clinical msp genotypes ( P <.001). Patients with periodontitis had higher levels of clinical msp genotype diversity than periodontitis‐free controls (Mann‐Whitney U ‐test, P <.05). The relative proportions of ' T. vincentii ' clinical msp genotypes were significantly higher in the control group than in the periodontitis group ( P =.018). In conclusion, our data clearly show that both healthy and diseased individuals commonly harbor a wide diversity of Treponema clinical msp genotypes within their subgingival niches.